(untitled) (Eurasian Medical Research Periodical, 2022)
The study was conducted on patients with type 2 diabetes at Kirkuk General Hospital, through the period from November 2017 to February 2018. The total number of diabetic patients was 30 (16 males and 14 females), and their ages ranged between (15- 90 year). These patients were compared with 15 healthy individuals (10 males and 5 females). The results of the current study showed that type 2 diabetes had a significant effect on kidney function and raised glucose, urea and creatinine levels to high levels compared to the control group, which amounted to 306.37 mg/dL, 41.87 and 2.25 mmol/L, and the patients’ age and body mass index significantly affected the variables studied. While there were no significant differences between the two sex groups among patients and healthy subjects, the results of the Pearson correlation coefficient analysis showed the presence of significant and direct correlations between the study factors and their variables.